Kearifan Lokal Sebagai Bentuk Kontrol Sosial Masyarakat Sukolilo - Riris Tiani (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Tradition ceremony Meron one of the rituals held every month Maulud.This tradition is done by the people of Sukolilo village Pati which aims to commemorate the birthday one of Prophet. Data collection methods used were interviews and documentation analyzed using etnolinguistic theory. Based on the analysis of local wisdom of the Meron tradition of Sukolilo society in Pati Regency, it can be concluded that the form of local traditions of Meron wisdom culture develops in the form of the traditional phrase which is realized in traditional ceremonial ritual and traditional feast, preserving traditional technology in this case through gunungan offerings architecture. While the function of the cultural tradition is 1) usage or how to perform a ceremony or ritual, 2) folkways or habits in living the tradition of ancestors that are still preserved, 3) norms or norms related to the custom known and obeyed by the community.